My big fat Greek wedding [videorecording (DVD)] - Zwick, Joel; Vardalos, Nia, 1962-; Corbett, John, 1961-; Kazan, Lainie (HBO Video, 2002)
Toula is a quiet, devoted daughter in a big, crazy Greek family. Working in her father's restaurant, she hides behind her family and keeps the world at a distance. One day at the restaurant she finds herself pouring coffee for a man who inspires her to change her life, and the way she sees the world ... forever.